Scaling up essential surgery in rural Africa: outcomes of a novel regional initiative - Kintu-Luwaga, Ronald; Semakula, Daniel; Makor, Ajak; Mwanje, Wilbrod (IJS Global Health, 2023)
South Sudan, like most of rural Africa, has a high surgical disease burden and profound unmet surgical needs. This is against a background of weak surgical service delivery systems, especially in the harder-to-reach areas. Here it is further fueled by armed conflict and poverty. The surgical service delivery models applied so far have not adequately improved surgical care. Through the Intergovernmental Authority on Development Regional Initiative for Capacity Building, a surgical team was deployed to Kuajok Hospital in Warrap state. The team mentored South Sudanese health workers for 2 years while working together with other agencies operating in the locality to improve surgical services. This paper is an account of the capacity building process for surgical service improvement at this site, from 2015 to 2017.